Evaluasi Implementasi Sistem Informasi Manajemen Rumah Sakit dengan Metode HOT-Fit di RSU Muhammadiyah Babat - Muhamad Ganda Saputra; Nihayatul Munaa; Yuni Anggraini; Faizatul Ummah; Nahardian Vica Rahmawati; Ari Kusdiyana; Nuryati Nuryati (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
This study aimed to know evaluation the implementation of the HMIS using the HOT-FIT method at Muhammadiyah General Hospital of Babat. This was a quantitative research with a cross sectional survey design. The sample was 59 respondents obtained by proportionate stratified random sampling. The independent variables were human, organization, and technology. The dependent variable was the net benefit from HMIS. The instrument was a closed questionnaire. The results showed that 42 respondents (71%) considered human variable good, 50 respondents (85%) considered organization variable good, 47 respondents (80%) consider technology variable goo, and 56 respondents (95%) stated that net benefit was good. The findings were analyzed by using multiple linear regression with the T and F tests (α = 0.05). The results of the T tests there is 1 variable that affects on net benefit, technology (p=002. Ehile 2 valiable which had an effect on net benefits, human (p=0.889), organization (p=0.126). In the results of the F tests s, it was found that there was a relationship between the independent variables simultaneously with the system benefits of p = 0.000. It is hoped that the results of this study can be further improve on the system, especially on technological factors that have a very large influence on system implementation as adding more sophisticated features and facilities in the implementing HIMS so that thr system cam run very well.